2021
DOI: 10.1021/acs.est.0c05111
|View full text |Cite
|
Sign up to set email alerts
|

Medium- and Short-Chain Chlorinated Paraffins in Mature Maize Plants and Corresponding Agricultural Soils

Abstract: For the most complex artificial chlorinated environmental contaminants, much less is known for medium-chain CPs than short-chain CPs. In this research, the spatial distributions of MCCPs and SCCPs in farmland soil and maize leaves near a CP production facility were found marginally influenced by seasonal winds. The levels of ∑MCCPs and ∑SCCPs were in the ranges of <1.51−188 and 5.41−381 ng/g dw for soils; and 77.6−52930 and 119−61999 ng/g dw for maize leaf, respectively. Bioaccumulation and tissue distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Due to the selectivity of CPs monomer accumulation pattern, there were clear differences in the distribution of homologues of edible fungi and culture materials with different components. Previous studies have found that the contribution of soil to CPs pollution in maize plants was secondary, mainly due to air pollution (W. Chen et al., 2021). Therefore, we speculated that due to the short growth cycle of edible fungi, culture materials may not be the main source of CPs and may accumulate and migrate from the environment to the organism.…”
Section: Resultsmentioning
confidence: 96%
“…Due to the selectivity of CPs monomer accumulation pattern, there were clear differences in the distribution of homologues of edible fungi and culture materials with different components. Previous studies have found that the contribution of soil to CPs pollution in maize plants was secondary, mainly due to air pollution (W. Chen et al., 2021). Therefore, we speculated that due to the short growth cycle of edible fungi, culture materials may not be the main source of CPs and may accumulate and migrate from the environment to the organism.…”
Section: Resultsmentioning
confidence: 96%
“…SCCPs are widely used in these industries, and thus might be responsible for the higher concentration of SCCPs observed at Site M6 than at sites in the E‐waste dismantling areas. The concentrations of SCCP in urban and industrialized areas of Zhejiang, China, were higher than those in farmland soil near a CP production facility in Liaocheng, China (5.4–381 ng/g dw, mean = 28 ng/g dw) (Chen et al, 2021), coastal soil in the intertidal zone of Shandong Peninsula, China (50–266 ng/g, mean = 94 ng/g) (Zhao et al, 2019), urban soils (<DL–615 ng/g, mean = 16 ng/g) (Wang et al, 2014) and suburban soils (ND–697 ng/g, median = 3.5 ng/g) (Wang et al, 2017) of Shanghai, China and topsoils from Guangzhou (1.5–26 ng/g with the mean concentration of 10 ng/g dw) and Chengdu (0.22–3.3 ng/g dw, mean concentration = 1.4 ng/g dw) (Huang et al, 2016). The concentrations of SCCP in soil of industrialized and urban areas in this study were of the same order of magnitude as those in the soil nearby factories of a non‐ferrous metal recycling park located in Hebei, China (121–5159 ng/g, mean of 597 ng/g) (Weng et al, 2022), soils from the rural dumpsites and urban landfill on the Tibetan plateau (57–1348 ng/g dw, mean concentration = 434 ng/g dw) (Li, Xu, et al, 2021), soil samples collected from the Yangkou Chemical Industrial Park of Jiangsu Province, China (38–996 ng/g dw, mean concentration = 225 ng/g dw) (Huang et al, 2020), soil samples collected from the outside of a CP production plant in Shandong, China (102–441 ng/g, mean = 248 ng/g), ambient surface soils collected from the surrounding area of a CP production plant located in Dalian City, northeast China (25–482 ng/g with the mean concentration of 142 ng/g) (Xu et al, 2016), backfilled farmland soil samples collected near the sewage outlet of the highly polluted Ya'Er Lake (mean concentration = 357 ng/g dw) (Li, Chen, et al, 2021), soil samples collected from Dongguan City, South China (mean concentration = 172 ng/g) (Wu et al, 2020) and farm soils collected from a wastewater irrigated area in the southeast suburbs of Beijing, China (160–1450 ng/g) (Zeng et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Partial least squares discriminant analysis (PLS-DA) with variable importance (VIP) values was used to identify the difference in soil metabolites (Darnaud et al, 2021). The PLS-DA model was validated with a permutation test (n = 200), R 2 data are larger than Q 2 data, and the intercept of Y and Q 2 was less than 0 (R 2 intercept = 0.9576, Q 2 intercept = −0.3811), which means the model was fit and not overfitting (Chen et al, 2021). The alpha diversity indices including Chao1 and inverse Simpson index (or InvSimpson for short) were calculated by the R program package "vegan" (Oksanen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%